Reinventing your primary care practice: becoming an MDCEO™ - Conard SE; Courtney MR (Dove Medical Press, 2013)
Scott E Conard,1 Maureen Reni Courtney21ACAP Health, Dallas, 2College of Nursing, University of Texas, Arlington, TX, USAAbstract: Primary care medicine in the United States is undergoing a revolutionary shift. Primary care providers and their staff have an extraordinary chance to create and participate in exciting new approaches to care. New strategies will require courage, flexibility, and openness to change by every member of the practice team, especially the lead clinician who is most often the physician, but can also be the nurse practitioner or physician's assistant. Providers must first recognize their need to alter their fundamental identity to incorporate a new kind of leadership role—that of the MDCEO™ (i.e., the individual clinician who leads the practice to ensure that quality, service, and financial systems are developed and effectively managed). This paper provides a practical vision and rationale for the required transition in primary care, pointing the way for how to achieve new practice effectiveness through new leadership roles. It also provides a model to evaluate the status of a primary care practice. The authors have extensive experience in working with primary care providers to radically evolve their clinical practices to become MDCEOs™. The MDCEO™ will articulate the vision and strategy for the practice, define and foster the practice culture, and create and facilitate team development and overall high level functioning. Each member of the team can then begin to lead their part of the practice: a 21st century population-oriented, purpose-based practice resulting in increased quality of care, improved patient outcomes, greater financial success, and enhanced peace of mind.Keywords: primary health care organization and administration, health care reform, leadership, patient-centered care